Role of Cytochrome Modulators in Altering the Occurrence of Cataract in Rats - Kanchan Gupta; Shivani Juneja; G S Bajwa; Sandeep Kaushal (Journal of Clinical and Diagnostic Research, 2015)
Background: Cataract is one of the primary causes of blindness all over the world. It indicates the onset of secondary complications of diabetes. The only treatment available is surgery as there are no satisfactory drugs which can prevent or retard the initiation and maturation of cataract. It was hypothesized that cytochrome P 450 (CYP) inducers or inhibitors can modify the cataract occurrence by accelerating or delaying the occurrence of cataract respectively. Objective: To study the effect of two commonly used drugs, phenytoin (CYP inducer) and ciprofloxacin (CYP inhibitor) on the initiation and maturation of cataract with the galactoseinduced cataract model. Materials and Methods: The experiment was conducted in 24 new born male Wistar rats. Cataract formation was induced with a 50% galactose diet. The rats were randomized into four groups of 6 rats each: Group 1 rats received a normal diet; Group 2, 3 and 4 rats received 50% galactose diet day 23 onwards. In addition, Group 3 rats were pre-treated with ciprofloxacin (20mg/kg) and Group 4 rats were pre-treated with phenytoin (50mg/kg) day 18 onwards once a day orally. The appearance of cataract was checked daily with an ophthalmoscope. The maturation pattern was examined using Fundus Fluorsen Angiographer (FFA). The cataract was graded according to Sippel's classification. The experimental and control groups were compared by chi square test and the results were considered significant at p< 0.05. Results: The initiation of cataract was significantly delayed with ciprofloxacin as compared to galactose; however, there was no difference in the maturation pattern of cataract in both the groups. In spite of being a CYP inducer, the initiation of cataract was not accelerated in phenytoin group. Rather, it was significantly delayed and the cataract did not progress to stage 5 even on 30th day of galactose administration Conclusion: CYP450 modulators have a significant effect on the initiation of cataract without significantly altering the maturation pattern. It is not reasonable to extrapolate the results of one enzyme inhibitor or inducer to other CYP modulators. Hence, further studies are needed to identify the pharmacological profile of various CYP modulators on the occurrence of cataractogenesis.